2001
DOI: 10.14411/eje.2001.064
|View full text |Cite
|
Sign up to set email alerts
|

Comparative dispersal and larvicidal activity of exotic and Azorean isolates of entomopathogenic nematodes against Popillia japonica (Coleoptera: Scarabaeidae)

Abstract: Abstract. The Japanese beetle, Popillia japonica Newman, is an introduced pest on Terceira, one of nine islands in the Azorean Archipelago. Research conducted on Terceira indicates that entomopathogenic nematodes in the families Steinemematidae and Het erorhabditidae provide good to excellent control of Japanese beetle larvae, but the species that have been evaluated are not native to the Azores. An efficacious species that is native to the archipelago might provide increased capabilities for persisting and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…While the response of S. glaseri in Koppenhöfer et al (2000) was very similar to the one observed in our study, the response of H. bacteriophora was different in as much as it showed lower dispersal but a stronger relative response. Using a horizontal experimental setup, Lacey et al (2001) found a similar relative response as in our study with a 10-fold increase in the presence of third-instar P. japonica for S. glaseri (NC1 strain) and only a 2-fold increase for H. bacteriophora (AZ162 isolate). However, H. bacteriophora was more active resulting in twice as many H. bacteriophora than S. glaseri dispersing toward the host.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…While the response of S. glaseri in Koppenhöfer et al (2000) was very similar to the one observed in our study, the response of H. bacteriophora was different in as much as it showed lower dispersal but a stronger relative response. Using a horizontal experimental setup, Lacey et al (2001) found a similar relative response as in our study with a 10-fold increase in the presence of third-instar P. japonica for S. glaseri (NC1 strain) and only a 2-fold increase for H. bacteriophora (AZ162 isolate). However, H. bacteriophora was more active resulting in twice as many H. bacteriophora than S. glaseri dispersing toward the host.…”
Section: Discussionsupporting
confidence: 85%
“…The nematodes used in this study are cruisers based on their attraction to host volatiles or hosts and their mobility and distribution throughout the soil profile (e.g., Grewal et al, 1993a;Lewis et al, 1993;Westermann, 1995;Lacey et al, 2001;Koppenhöfer and Fuzy, 2003b). Results from our study should help explain differences in nematode efficacy against different white grub species and thereby help to optimize nematode species-target host matching for improved biological control.…”
Section: Introductionmentioning
confidence: 99%
“…In general, pupae of white grubs are more susceptible to EPN than active feeding larvae (Lacey et al 2001;Lee et al 2002;Koppenhöfer and Fuzy 2004). Our bioassays yielded similar results for all isolates.…”
Section: Discussionsupporting
confidence: 59%
“…The positive influence of host insect cues on the migration of EPN is well documented (e.g. Lacey et al 2001;Koppenhöfer and Fuzy 2008). Nematode attraction in response to insects is reported to be due to host cues like CO 2 (Gaugler et al 1980; Lewis et al 1993) and/or gut fluids (Grewal et al 1993a, b).…”
Section: Discussionmentioning
confidence: 98%
“…and Heterorhabditis bacteriophora have been evaluated for effectiveness against P. japonica in the Azores (Simões et al, 1993) and in Piedmont (B. Cavagna, Regione Lombardia, pers. In the Azores efforts have been made to find endemic entomopathogenic nematodes for the control of P. japonica (Lacey et al, 2001). Steinernema glaseri and Steinernema carpocapsae both reduced larval populations when applied in September but proved ineffective during the colder months (November to February) (Simões et al, 1993).…”
Section: Biological Controlmentioning
confidence: 99%